2002
DOI: 10.1161/01.cir.0000034508.55617.65
|View full text |Cite
|
Sign up to set email alerts
|

ARBITER: Arterial Biology for the Investigation of the Treatment Effects of Reducing Cholesterol

Abstract: Background-Whether marked LDL reduction to levels well below 100 mg/dL would further reduce the burden of cardiovascular disease is controversial. We compared the effects of 2 statins with widely differing potencies for LDL reduction (pravastatin 40 mg/d and atorvastatin 80 mg/d) on carotid intima-media thickness (CIMT). Methods and Results-This was a single-center, randomized, clinical trial of 161 patients (mean age, 60 years; 71.4% male; 46% with known cardiovascular disease) that met National Cholesterol E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 511 publications
(66 citation statements)
references
References 42 publications
2
60
0
4
Order By: Relevance
“…45 Data from the Arterial Biology for the Investigation of the Treatment Effects of Reducing Cholesterol (ARBITER-2) study demonstrated that ER-niacin added to statin therapy may halt the progression of atherosclerosis, as measured by carotid intimamedia thickness among CHD patients with low HDL-C levels. 47 After 1 year of treatment, mean carotid intima-media thickness increased in the statin-only group but not in those treated with ER niacin. The addition of ER-niacin to background statin was well-tolerated with adherence exceeding 90%.…”
Section: Combination Therapymentioning
confidence: 89%
See 1 more Smart Citation
“…45 Data from the Arterial Biology for the Investigation of the Treatment Effects of Reducing Cholesterol (ARBITER-2) study demonstrated that ER-niacin added to statin therapy may halt the progression of atherosclerosis, as measured by carotid intimamedia thickness among CHD patients with low HDL-C levels. 47 After 1 year of treatment, mean carotid intima-media thickness increased in the statin-only group but not in those treated with ER niacin. The addition of ER-niacin to background statin was well-tolerated with adherence exceeding 90%.…”
Section: Combination Therapymentioning
confidence: 89%
“…The addition of ER-niacin to background statin was well-tolerated with adherence exceeding 90%. 47 The National Institutes of Health (NIH) is sponsoring the Atherothrombosis Intervention in Metabolic Syndrome with Low HDL Cholesterol/High Triglyceride and Impact on Global Health Outcomes (AIM-HIGH) trial which will evaluate the merits of simultaneously lowering LDL and raising HDL cholesterol levels, in patients randomized to ER-niacin plus simvastatin or to simvastatin alone. The Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial is testing fenofibrate plus a statin versus a statin alone in patients with type 2 diabetes.…”
Section: Combination Therapymentioning
confidence: 99%
“…Результат более чем впечатляющий, если учесть, что, например, в исследовании ARBITER применение атор-вастатина по 80 мг/сут приводило к двукратному сни-жению ХС ЛПНП, при этом средняя ТИМ каротидных ар-терий уменьшалась через 6 мес терапии на 0,016 мм, а через год -на 0,034 мм по отношению к исходным значениям [14]. Можно также вспомнить исследование ARBITER 2, в котором прием никотиновой кислоты по 1000 мг/сут приводил к приросту ХС ЛПВП на 21%, при этом через год терапии средняя ТИМ каротидных ар-терий оказалась только на 0,03 мм меньше, чем в груп-пе плацебо [15].…”
Section: продолжительность монотерапии урсодезоксихолевой кислотойunclassified
“…Можно также вспомнить исследование ARBITER 2, в котором прием никотиновой кислоты по 1000 мг/сут приводил к приросту ХС ЛПВП на 21%, при этом через год терапии средняя ТИМ каротидных ар-терий оказалась только на 0,03 мм меньше, чем в груп-пе плацебо [15]. Примечательно, что в обоих этих ис-следованиях оценка каротидных ультрасонограмм осу-ществлялась с использованием «слепого» метода [14,15], тогда как исследование B.D. Ozel Coskun и соавт.…”
Section: продолжительность монотерапии урсодезоксихолевой кислотойunclassified
“…Specifically, there have been three clinical trials in subjects with known CAD comparing the same therapies: pravastatin (40 mg/day) and atorvastatin (80 mg/day). Two of these studies used ultrasound to assess the progression of coronary atherosclerosis, one (ARBITER) with carotid ultrasound (Taylor et al, 2002) and one (REVERSAL) with coronary IVUS (Nissen et al, 2004). Both studies showed significant differences in the progression of atherosclerosis, favoring atorvastatin (80 mg/day).…”
Section: Correlation Between Carotid Intima-media Thickness Intrmentioning
confidence: 99%